2018
DOI: 10.2174/1871527317666180726095734
|View full text |Cite
|
Sign up to set email alerts
|

The Dopaminergic Dysfunction and Altered Working Memory Performance of Aging Mice Lacking Gamma-synuclein Gene

Abstract: Therefore most likely these dysfunctions are associated with a reduction in the highefficient learning performance in tests that require intact working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…More recent studies show that single γ-Syn knockout mice display low levels of anxiety-like behavior, high exploratory activity, and enhanced habituation [29]. In addition, inactivation of the γ-Syn gene led to the improvement of working memory in mice, effects linked to changes in DA function [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies show that single γ-Syn knockout mice display low levels of anxiety-like behavior, high exploratory activity, and enhanced habituation [29]. In addition, inactivation of the γ-Syn gene led to the improvement of working memory in mice, effects linked to changes in DA function [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicated that there is an association between plasma levels of both α-synuclein and γ-synuclein and the severity of ASD compared to the control group as shown in Figure 3a–f. Previous studies also reported a correlation between both α-synuclein or γ-synuclein in memory, cognitive functions, and social communication [10, 27]. The association between intellectual disabilities and synaptic dysfunction in autistic children was found to be significant [28].…”
Section: Discussionmentioning
confidence: 85%
“…In addition, α-synuclein has been reported to inhibit certain signaling pathways of brain-derived neurotrophic factor (BDNF), leading to dopaminergic neuronal death, which causes neurotoxicity in PD [8]. Also, the overexpression of α-synuclein and γ-synuclein is associated with cognitive deficits [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Professor The most recent scientific interests of Professor Aliev were in the fields of cancer cell biology, biochemistry, and the functional morphology of cells and tissues. He investigated the structure and functions of endothelial cells [33,35,44,50], smooth muscle cells [51,52], neurons [3,45,53,54], glial cells [55][56][57][58], and macrophages [47,50]. He was keen to address the most urgent health problems.…”
mentioning
confidence: 99%
“…Following this, Gjumrakch received postdoctoral training under the prestigious British Heart Foundation Grant Program in the University College London (advisor Professor Geoffrey Burnstock), specializing in medicine.Professor Aliev possessed an encyclopedic knowledge in a wide range of scientific fields; however, his main research focus was linked to the development of unique technologies and treatment protocols for age-associated diseases. He was recognized internationally for his work in the fields of gerontology[1][2][3][4][5], oncology[6][7][8][9][10][11][12][13][14][15], cardiovascular diseases[16][17][18][19], endocrinology[2,20,21], and neurodegenerative diseases[15,20,[22][23][24][25][26][27][28][29][30][31][32]. His research publications on the role of vascular and mitochondrial factors in the pathogenesis of aging[2,3,5], atherosclerosis[33,34], ischemia-reperfusion[18,[35][36][37], stroke…”
mentioning
confidence: 99%